ЕКОНОМІЧНИЙ ЗМІСТ ЕФЕКТИВНОСТІ ПУБЛІЧНИХ ЗАКУПІВЕЛЬ ТА ЗАСАДИ ЇЇ КОМПЛЕКСНОГО ОЦІНЮВАННЯ - В.Ю. Халіна (Market Infrastructure, 2026)
The study aims to deepen the theoretical foundations of public procurement efficiency and substantiate a comprehensive assessment approach in the context of results-oriented use of public funds. The research applies the methods of systematization, comparison, generalization, structural analysis and scientific abstraction. The relationships among savings, economy, effectiveness, efficiency, and public value are clarified. It is argued that the purchase price and nominal savings reflect only the initial financial outcome of a procurement procedure. They do not demonstrate whether the required goods, works, or services were delivered in full and on time, whether the contract achieved its intended purpose, or whether the relevant budget programme produced the expected results. Therefore, savings should be treated as a financial indicator rather than as a synonym for procurement efficiency. A multilevel approach is proposed that integrates procedural, budgetary and financial, contractual and performance-based, life-cycle, and strategic dimensions. These dimensions reflect, respectively, the quality of the procedure; compliance with budget allocations and value for money; completeness, quality and timeliness of contract implementation; operating, maintenance, and disposal costs; and the contribution to budget programme outcomes and public value creation. Relevant groups of indicators are identified for each dimension. The relationship between procurement planning, budget commitments, contract implementation, payments, budget execution, and final public outcomes is established. This links budget expenditure to measurable procurement outcomes. The scientific novelty lies in conceptualizing procurement efficiency as an integrated economic category that combines immediate financial results with contractual, long-term, and societal effects. The proposed approach may be used by contracting authorities, managers of public funds, and financial control bodies to improve the assessment of procurement outcomes and the efficiency of state and local budget execution.